2022
DOI: 10.3389/fphys.2022.1032383
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10: Possible functions in enamel development

Abstract: ADAM10 is A Disintegrin And Metalloproteinase (ADAM) family member that is membrane bound with its catalytic domain present on the cell surface. It is a sheddase that cleaves anchored cell surface proteins to shed them from the cell surface. ADAM10 can cleave at least a hundred different proteins and is expressed in most tissues of the body. ADAM10 is best characterized for its role in Notch signaling. Interestingly, ADAM10 is transported to specific sites on the cell surface by six different tetraspanins. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…One reason for this is a decrease in the von Willebrand factor (VWF) due to adsorption by excess platelets [4]. In addition, the proteolytic enzymes a disintegrin and metalloproteinase domain-containing protein (ADAM) 10 [5], and ADAM17 [6] are secreted by excessively increased platelets, resulting in the degradation of high-molecular weight-VWF (HMW-VWF) multimer [7]. Another possible mechanism is the excessive Int.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this is a decrease in the von Willebrand factor (VWF) due to adsorption by excess platelets [4]. In addition, the proteolytic enzymes a disintegrin and metalloproteinase domain-containing protein (ADAM) 10 [5], and ADAM17 [6] are secreted by excessively increased platelets, resulting in the degradation of high-molecular weight-VWF (HMW-VWF) multimer [7]. Another possible mechanism is the excessive Int.…”
Section: Introductionmentioning
confidence: 99%
“…The A Disintegrin And Metalloprotease (ADAM) family includes 22 members, but only 12 encode active enzymes, with ADAM10 being one of the most characterized members [ 10 ]. A constitutive expression of ADAM10 is found as a transmembrane in different cells, such as immune cells and renal tubule cells, with at least 40 substrates [ 11 ]. The activation of ADAM10 initiates an inflammatory and fibrotic response to renal diseases, including ARF, and recent studies have shown a link between ADAM10 and coagulation in kidney disease [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%